KOMUNIKASI DALAM PENERAPAN SISTEM JAJAR LEGOWO DI DESA MURNI JAYA KECAMATAN TUMIJAJAR KABUPATEN TULANG BAWANG BARAT - Erika Dwi Alviana; Tri Pujiana; Dwi Arianti; Helvi Yanfika (Universitas Galuh Ciamis, 2019)
The purpose of this study was to find out the communication process between extension agents and farmers in implementing the Jajar Legowo system in Murni Jaya, Tumujajar District, Tulang Bawang Barat District. The location of the study was determined purposively. Data collection was conducted in November 2018. This type of research is qualitative research. Data collection techniques by conducting direct observations to the research site, deep interview interviews with the management of farmer and extension groups, and literature studies. The method of data analysis is descriptive qualitative. The focus of this research is the obstacle of communication between Mekar Jaya Jaya extension agents and Gapoktan in the implementation of the Jajar Legowo Planting System and the solution to deal with the problem. The results of the study showed that the communication carried out by the instructor was quite good, this was because the instructor had meetings with members of the farmer group once a month, carried out the program and continued the work. Whereas farmers who did not want to implement the Jajar Legowo Planting System were caused by the complex nature of the innovation and the cost of implementing the innovation was greater than using the previous planting system, so there were still doubts by farmers to implement the innovation. Efforts are being made to overcome these obstacles, namely the need to improve farmers' perceptions of the Jajar Legowo Planting System, extension workers need to increase the intensity of assistance to farmers, and also need to control and evaluate rice farming carried out by rice farmers in Murni Jaya Village.